Autonomy-Support and Student Motivation in Swedish EFL Classrooms - Brunzell,Anthon (2022)
Despite discussions in Swedish education that English teaching in Sweden does not provide students with relevant contents that support their learning and motivation, no measurements have been made when it comes to the connection between Swedish students’ L2 motivation and pedagogy. The study at hand used a measure of self-determination to examine the L2 motivation of 159 Swedish upper secondary school students taught by six different teachers and a measure of perceived autonomy-support and the relationship between these factors. In addition, the six teachers answered a questionnaire about their autonomy-supportive efforts in the classroom and these were subsequently given a rank on an autonomy-supportive attitude scale. A between-groups analysis compared the different autonomy-supportive attitudes and their effect on students’ motivation. Results-wise, students were (1) in general highly motivated to learn English extrinsically but also because the subject was inherently enjoyable. Students also felt autonomy-supported by their teachers; (2) Students’ amotivation, perceived autonomy-support and self-determination had a weak relationship with each other (r =0.333; r = −0.209; r = −0.249; p < 0.01); (3) A higher amotivation in groups was found to be the effect of having a teacher with an attitude in-between autonomy-supportive and controlling (p < 0.05). Effect size was not measured because of data loss. These results are discussed with plausible implications in teaching practice.
Keywords: EFL; self-determination; autonomy-support; attitudes; Sweden